ANALYSIS OF THE WHITE STORK POPULATION (CICONIA CICONIA (LINNAEUS, 1758) IN THE FERGANA VALLEY AND OTHER REGIONS OF THE REPUBLIC AND FACTORS AFFECTING THE DECLINE IN THE NUMBER OF THE SPECIES (Universal International Scientific Journal, 2026)
This article analyzes the distribution, ecological status and population dynamics of thewhite stork (Ciconia ciconia) in the Ferghana Valley and in other regions of Uzbekistan. The naturalhabitat, food sources, and migration routes of white storks were studied. The study analyzedanthropogenic and natural factors contributing to the decline of the species, such as habitat reduction,power transmission networks, exposure to pesticides, depletion of water resources, reduction of foodsupply and climate change. The article has developed scientifically based proposals for the conservationand restoration of the white stork population. The results show that the white stork is a bioindicator birdthat occupies an important place in the biodiversity of Uzbekistan, the number of which is closely relatedto environmental sustainability
Keywords: white stork; Ciconia ciconia; population